Pregled in analiza izbranih podatkovnih zbirk ter predmetnih oznak za področje lesarskih znanosti in tehnologije - Bartol, Tomaž (Zbornik gozdarstva in lesarstva, 2007)
End-users should be able to identify the most relevant scientific and technical information resources. They must understand database structure, query techniques, controlled dictionaries, terminology and indexing schemes. In the present article, we review principal characteristics of the following information systems: bibliographic databases (Agricola, Agris, Cab Abstracts (CABI), Compendex, Inspec, Iconda, statistical collections Eurostat and Faostat, and technical standards and patents ISO and WIPO with regard to the field of wood sciences or processing of forest products. Differences in database fields and search characteristics (search platforms, Boolean logic, prefixes, suffixes, wildcards) are described. Special attention is placed on subject headings in each respective database: narrow keywords (Descriptors, Heading Words, Controlled Terms, Keywords) and broader categories (Subject Categories, Concept Codes, CABI Codes, Classification Codes). Word counts are shown for the terms with the highest frequency of occurrences. This review promotes the use of additional databases, encourages employment of structured vocabularies, which should result in improved search results.
Keywords: geslovniki; indeksiranje; lesarstvo; podatkovne zbirke; predmetne oznake